2022
DOI: 10.3389/fbioe.2021.820892
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Preparation of Low-Molecular-Weight Laminaria japonica Polysaccharides and Evaluation of Its Effect on Modulating Intestinal Microbiota in High-Fat-Diet-Fed Mice

Abstract: Recent studies have shown that seaweed polysaccharides can ameliorate high-fat-diet (HFD)-induced metabolic syndromes associated with the regulatory function of gut microbiota. However, kelp, a natural source of seaweed polysaccharides, is highly viscous, making it difficult to prepare dietary fiber by simple degradation. Therefore, we developed a novel method of preparing low-molecular-weight polysaccharides from Laminaria japonica by combining high-pressure pretreatment and composite enzymatic degradation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The pathways involved in the microbiota affected by T2D mellitus were the same as those involved in the metabolites affected by T2D mellitus in serum metabolomics. The significantly increased Romboutsia bacteria content after GG polysaccharide treatment was negatively correlated with tauroursocholic acid, The significantly reduced Klebsiella content after FG polysaccharide treatment was positively correlated with uric acid, Romboutsia [ 24 ], and Klebsiella [ 10 ], which are qualities associated with T2D. These results indicated that T2D affected the metabolic environment in the body by affecting the gut microbiota, and the GG and FG polysaccharides were able to ameliorate the metabolites in the serum by regulating the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The pathways involved in the microbiota affected by T2D mellitus were the same as those involved in the metabolites affected by T2D mellitus in serum metabolomics. The significantly increased Romboutsia bacteria content after GG polysaccharide treatment was negatively correlated with tauroursocholic acid, The significantly reduced Klebsiella content after FG polysaccharide treatment was positively correlated with uric acid, Romboutsia [ 24 ], and Klebsiella [ 10 ], which are qualities associated with T2D. These results indicated that T2D affected the metabolic environment in the body by affecting the gut microbiota, and the GG and FG polysaccharides were able to ameliorate the metabolites in the serum by regulating the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…After acclimatization for 3 days, these mice were randomly divided into three groups namely control group (Con), Cr (VI)-induced group (Cr), seaweed polysaccharide treatment group (SP, 200 mg/kg). The dosage of seaweed polysaccharide and Cr (VI) refers to the previous research with slight improvements ( Ben et al, 2016 ; Fu et al, 2021 ). The proportion of male and female in each groups was 1:1.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies indicated that seaweed polysaccharide has anti-inflammatory, antiviral, immunomodulatory and anti-tumor effects ( Lomartire and Goncalves, 2022 ). Moreover, recent research on seaweed polysaccharide also showed its vital roles in the gastrointestinal disease and improve antioxidant ability ( Fu et al, 2021 ). Although increasing evidence showed the positive role of seaweed polysaccharide on the host health, it remains unclear whether seaweed polysaccharide can alleviate gut microbial imbalance caused by hexavalent chromium.…”
Section: Introductionmentioning
confidence: 99%